Authentic leadership and flourishing: Do trust in the organization and organizational support matter during times of uncertainty? - Kleynhans, Deon J.; Heyns, Marita M.; Stander, Marius W. (Frontiers in Psychology, 2022)
Orientation: This study investigated the influence of authentic leadership on employee flourishing while considering the potential mediating effect of trust in the organization and organizational support as underlying mechanisms in an uncertain setting. Research purpose: To examine the relationship between authentic leadership and employee flourishing by evaluating the indirect effect of organizational support and trust in the organization as potential mediators. Motivation for the study: An authentic leadership approach, organizational support, and trust in the organization may influence the flourishing of employees in uncertain times. Increasing the comprehension of the possible interaction effect of organizational support and trust in the organization in the relationship between authentic leadership and employee flourishing may improve individual and organizational efficiency. Research approach/design and method: A quantitative, cross-sectional survey design was applied in this study. The sample comprised 314 employees in a noteworthy South African steel manufacturing entity. The Authentic Leadership Inventory, Workplace Trust Survey, Flourishing-at-Work Scale, and the Job Demands-Resources Scale were administered. Main findings: The findings of this study suggest that authentic leadership was a significant predictor of employee flourishing through organizational support and trust in the organization. Practical/managerial implications: This research illuminates the potential value-adding contribution of an authentic leadership style in promoting a trust-filled relationship between team members and their organization and the support they experience from their employer. Despite the prevailing precarious context, working under the mentioned conditions might result in the increased flourishing of employees. Contribution/value-add: The analyses of the mentioned relationships might assist businesses in optimizing the resources required to improve employee and organizational performance. Additionally, the exploration of organizational support in conjunction with organizational trust raises our understanding of the possible influence these elements can have in enhancing employee flourishing in the workplace.